The relationship between the quality of life and self-efficacy of women, younger and older, affected by Hansen's disease - Joachim, Cecilia (Animo Repository, 2001)
The relationship between Quality of Life and Self-Efficacy is studied among women affected by Hansen's disease.Through a purposive sampling method, 181 women between 16-68 years participated in the study. Of this age range, 94 were below 30 years and 84 were above 31 years. The women were all affected by Hansen's disease being themselves patients or related to patients. The Quality of Life Questionnaire constructed by the World Health Organization (WHOQOL-100), and the Self-Efficacy Scale by Schwarzer and Jerusalem (1993), were the two instruments used. Means, standard deviations, t-test, and Pearson 'r' Product Moment Correlation were employed to analyze the data. The results revealed that the Quality of Life of the women inspite of Hansen's disease was good. The younger women had better Quality of Life when compared to the older women in the Physical, Social Relationships, Level of Independence, Environmental domains and the perception of the Overall quality of life and health. The difference in the psychological and spiritual domains did not reach the significant level. The Self-Efficacy level of the women was good since they were able to cope with stressful consequences of Hansen's disease, and age made no difference. The relationship between the Quality of Life domains and Self-Efficacy showed that social support from the family and community, meaningful spiritual and religious beliefs, and a psychological hardiness helped them to cope with the effects of an intrusive disease like Hansen's disease. The relationship between Self-Efficacy and the Level of Independence domain as students/workers living in the community of Tala was good, but they felt curtailed as persons affected by the disease. As members of Tala-Caloocan community and as persons affected by Hansen's disease they felt supported and efficacious. As students and workers, however they did not feel efficacious. In conclusion, the women living in the community of Tala were capable of coping with Hansen's disease and maintaining a good Quality of Life revealed in their high level of Self-Efficacy. Although affected by the disease, the younger women fared better than the older. The spiritual, psychological and social relationships domains revealed a strong positive relationship and indicated that the culture and values of the women may have enabled them to use their inner resources and find meaning even in their adversity. The social support and the environment of Tala helped them to manifest a strength that seems characteristic of the Filipino women in the management of Hansen's disease. Based on the conclusions of the study, recommendations have been made for the benefit of the women affected by Hansen's disease, the counseling profession and other research possibilities in similar health related areas.